Mathew Pintauro: capstone - Pintauro, Mathew, artist and filmmaker (Colorado State University. Libraries, 2016)
The artist's statement: As an artist I strive to make my work as aesthetically pleasing as possible. I try to spread my technical knowledge over as many different kinds of media as possible, combining them in certain situations to achieve a unique look. With illustration as a background, I have made use of these skills to complement my design and electronic art abilities. I enjoy making crisp, clean work that pops visually. I strive for high contrast and bold imagery to make my work stand out as much as possible. I have an illustration interest in both two dimensional and three dimensional graphics.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Apogee - A montage video has no spoken word; Video Installation video has no audio.
To request a transcript for Waypoint; History of the Mobile Network; Demo Reel 2016, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: electronic art